Massive superstring vertex operator in D = 10 superspace - Berkovits, Nathan [UNESP]; Chandía, Osvaldo (Springer Nature, 2002)
Using the pure spinor formalism for the superstring, the vertex operator for the first massive states of the open superstring is constructed in a manifestly super-Poincaré covariant manner. This vertex operator describes a massive spin-two multiplet in terms of ten-dimensional superfields. © SISSA/ISAS 2002.
Keywords: Superspaces; Superstrings and Heterotic Strings